Pengaruh Gaya Kepemimpinan Karismatik, Karakteristik Individu, dan Karakteristik Pekerjaan Terhadap Kinerja Karyawan PT. Elnusa Petrofin Bengkulu - Dafa Saelendra; Syofian Syofian; Janusi Waliamin (Jurnal Simki Economic, 2023)
The purpose of this study is to determine how much influence Charismatic Leadership Style, Individual Characteristics and Job Characteristics have on Employee Performance at PT. Elnusa Petrofin Bengkulu. The variables of this study are Charismatic Leadership Style, Individual Characteristics and Job Characteristics. The method used in this research is distributing questionnaires. This research is a quantitative approach research. The research population is all employees of PT. Elnusa Petrofin Bengkulu, 50 samples using the saturated sample method. The analytical tool used in this study uses SPSS 22. The results of the study show that (1) the Charismatic Leadership Style has a significant effect on the performance of PT. Elnusa Petrofin Bengkulu, (2) Individual characteristics have no significant effect on the performance of employees of PT. Elnusa Petrofin Bengkulu(3) Job characteristics have no significant effect on the performance of employees of PT. Elnusa Petrofin Bengkulu (4) Charismatic Leadership Style, Individual Characteristics and Job Characteristics simultaneously influence the performance of PT. Elnusa Petrofin Bengkulu.